Poetry in Peer Groups to Reduce Suicide in a Latin American Context - Felipe Agudelo-Hernández; Mariana Rojas Echeverry; Matías Mejía Chaves (Creative Arts in Education and Therapy)
The objective of this study was to determine the impact on the reduction of mental health problems in adolescents who participate in support groups with poetry, those who participate in groups with other methodologies, and those who do not participate in support groups. This community trial, which performed in 2021, included 1252 adolescents, of whom 171 showed suicidal risk. Three groups were formed: a support group where poetry was included among the methods, a support group that worked on crafts, and a control group that did not participate in support groups. Greater recovery occurred in adolescents who participated in poetry. Recovery strategies can include artistic elements in their methodologies to increase effectiveness.